2012
DOI: 10.1063/1.4759003
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of radiative efficiency and deep level defect incorporation on threading dislocation density for InGaN/GaN light emitting diodes

Abstract: The influence of threading dislocation (TD) density on electroluminescence and deep level defect incorporation in the multi-quantum well regions of InGaN/GaN light emitting diodes (LEDs) was investigated. LED efficiency increased with decreasing TD density. To elucidate the impact of TD density on deep level defect incorporation and resulting radiative efficiency, deep level optical spectroscopy and lighted capacitance voltage measurements were applied to the LEDs. Interestingly, the concentration of all obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 16 publications
4
29
1
Order By: Relevance
“…But since the measurements are mostly done in the extrinsic excitation light range where the absorption coefficient is low the assumption of uniform excitation within the space charge region usually holds.) Such measurements were performed for MQW LED structures strongly differing by the dislocation density from 5.3 Â 10 8 to 2.9 Â 10 9 cm À2 [356]. External quantum efficiency measurements showed a much higher value for the lower dislocation density (see Fig.…”
Section: Deep Traps In Gan/ingan and Algan/algan Leds And Ldsmentioning
confidence: 98%
“…But since the measurements are mostly done in the extrinsic excitation light range where the absorption coefficient is low the assumption of uniform excitation within the space charge region usually holds.) Such measurements were performed for MQW LED structures strongly differing by the dislocation density from 5.3 Â 10 8 to 2.9 Â 10 9 cm À2 [356]. External quantum efficiency measurements showed a much higher value for the lower dislocation density (see Fig.…”
Section: Deep Traps In Gan/ingan and Algan/algan Leds And Ldsmentioning
confidence: 98%
“…[6][7][8] They have been shown to play a role in determining the quantum efficiency of LEDs and LDs and to take part in degradation occurring in these devices. [9][10][11][12] Not much is known regarding possible mechanisms of such dislocation-driven degradation. For MBE-grown LEDs, it has been reported that the loss of injection efficiency can be associated with the formation of dislocation bunches lying in the basal plane in the active region of the LEDs.…”
Section: Movement Of Basal Plane Dislocations In Gan During Electron mentioning
confidence: 99%
“…67 and 68, while the A coefficient was assumed to be roughly proportional to N disl 69 (see also the recent studies on the impact of TDD on LED efficiency presented in Refs. 63,[70][71][72][73][74][75][76]. Auger coefficients were not forced to be the same in LDD and HDD LEDs because, although nominally identical, secondary ion mass spectrometry (SIMS) measures suggest that the QWs of the LDD devices have probably a smoother profile, which could imply a lower Auger rate.…”
Section: D Simulation Studymentioning
confidence: 99%